Understanding economic development a global transition from poverty to prosperity? - White, Colin (Colin M.); Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2009)
This fascinating book considers one of the most important problems in economics: the inception of modern economic development. There is at present no satisfactory explanation of the inception of modern economic development; an excessive focus on either pure theory or on unique histories limits the explanatory power. This book realises the need to integrate the two approaches, moving beyond the proximate causes of economic theory to review the role in an analytic narrative of significant ultimate causes - geography, risk environments, human capital, and institutions.
pt. I. Introduction : theory and history -- pt. II. Ultimate causes : a fixed or malleable context -- pt. III. The driving forces -- pt. IV. Devising appropriate narratives -- pt. V. Conclusions.
Includes bibliographical references (p. 362-388) and index.
Keywords: Economic development; Globalization -- Economic aspects; Electronic books